(untitled) (Ustozlar uchun, 2026)
E-commerce has become one of the fastest-growing sectors of the global economy in recent years. The rapid development of digital technologies, the expansion of internet infrastructure, and the growing interest of consumers in online shopping have significantly accelerated the spread of electronic commerce. Today, billions of consumers around the world use online shopping platforms, and this process is fundamentally transforming the structure of international trade. According to recent estimates, around 2.7 billion people worldwide are expected to make purchases online by 2025, which represents nearly one-third of the global population. In addition, the total value of global e-commerce sales is projected to reach approximately 6.8 trillion US dollars by 2025, and this growth trend is expected to continue in the coming years.